Dissolved organic matter concentration, molecular composition, and functional groups in contrasting management practices of peatlands. Issue 6 (25th September 2021) - Negassa, Wakene; Eckhardt, Kai‐Uwe; Regier, Tom; Leinweber, Peter
Abstract: About 91, 300 ha of peatlands has been rewetted in western Europe since the mid‐1990s. Still, it is unknown how long‐term rewetting alters the dissolved organic matter (DOM) concentration, molecular composition, and functional groups. We examined these DOM characteristics in three peatland types subjected to 47‐ to 231‐yr drainage and 18‐ to 24‐yr rewetting to address this knowledge gap. Cold water‐extractable DOM was characterized by pyrolysis field ionization mass spectrometry (Py‐FIMS) and X‐ray absorption near‐edge structure (XANES) spectroscopy. The dissolved organic carbon (DOC) concentration in the rewetted forest peatland was 2.7 times higher than in the drained forest peatland. However, rewetting decreased the DOC concentrations by 1.5 and 4 times in the coastal peatland and percolation mire, respectively, compared with their respective drained peatlands at the topsoil horizons. The Py‐FIMS analysis revealed that all nine DOM compound classes' relative abundances differed between the rewetted and drained forest peatland with the lower relative abundances of the labile DOM compound classes in the rewetted forest peatlands. However, most DOM compound classes' relative abundances were similar between the rewetted and drained coastal peatlands and percolation mires. The XANES also revealed nine carbon and seven nitrogen functional groups with no apparent differences between the two contrasting management practices. The influence of drainage and rewetting on DOC concentration and molecular composition depends on peatland type, drainage period, rewetting intensity, and peat degradation status that should be considered in future research for understanding DOM transformation and transportation from degraded and restored peatland ecosystems. Core Ideas: Dissolved organic matter (DOM) concentrations and molecular compositions depend on degradation status in drained peatlands. Rewetting effects on DOM concentrations and molecular compositions differ with peatland types. Pyrolysis field ionization mass spectrometry reveals management effects on DOM molecular compositions compared with X‐ray absorption near‐edge structure.